Ritual Human Sacrifice in Mesoamerica Recent Findings and New Perspectives - Mendoza, Rubén G.; Hansen, Linda (Conflict, Environment, and Social Complexity, 2024)
XXX, 512 p. 210 illus., 10 illus. in color.